Set2 methyltransferase facilitates DNA replication and promotes genotoxic stress responses through MBF-dependent transcription - Pai, C; Kishkevich, A; Deegan, R; Keszthelyi, A; Folkes, L; Kearsey, S; De León, N; Soriano, I; de Bruin, R; Carr, A; Humphrey, T (Cell Press, 2017)
Chromatin modification through histone H3 lysine 36 methylation by the SETD2 tumor suppressor plays a key role in maintaining genome stability. Here, we describe a role for Set2-dependent H3K36 methylation in facilitating DNA replication and the transcriptional responses to both replication stress and DNA damage through promoting